Optimization of Digital Media in Islamic Religious Education Learning to Enhance Joyful Learning - Ulva Badi’ Rohmawati; Aya Mamlu’ah; Moh. Miftahul Choiri; Abdul Jalil; Sitti Atiyatul Mahfudoh (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the optimization of digital media in Islamic Religious Education (PAI) to enhance joyful learning at SMK YPM Bojonegoro. The main problem addressed in this research is the low level of student engagement due to teacher-centered learning practices. This study aims to analyze the role of digital media integration in creating an interactive, meaningful, and enjoyable learning environment. This issue is important given the growing need for innovative learning strategies that align with advances in educational technology. This research employs a qualitative case study design, using observation, interviews, and documentation as data collection techniques. The findings reveal that the use of digital media such as multimedia, interactive platforms, and audiovisual content is able to create a more enjoyable, engaging, and active classroom atmosphere. It also helps students better understand the material, provides more varied learning experiences, improves teacher–student relationships, encourages active participation, and enhances students’ understanding of PAI content. This study contributes to the development of innovative, technology-based teaching strategies in Islamic education. In conclusion, optimising digital media is essential for transforming learning into a more engaging, student-centred process and for improving both cognitive and affective learning outcomes.